História , memória e poder: Xavier da Veiga, o Arconte do Arquivo Público Mineiro - Marisa Ribeiro Silva (2006)
The objective of this text is the analysis of memory institucionalization in the XIX century through the creation of "memory places" and its political use as a disciplinary instrument. Specifically, the creation of the Arquivo Público Mineiro (APM) and the power games that surrounded its creation and the establishment of its collection. Moreover, following the footsteps of the institution´s first director José Pedro Xavier da Veiga, we will examine the historical idea that motivated the creation of the APM.